The Impact of Lead Pollution on Human Health (Environment) in Ancient Rome - Sič, Magdolna (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Having in mind that the lead coming from mines and foundries, from the water conducted thought the aqueducts and finally from food and wine, endangered to a great extent the health of Roman population, in this paper the author tackles the possible impact of lead from these sources onto human health (environment) in Ancient Rome, as well as the debated question whether the lead pollution was one of the factors that caused the fall of the Roman Empire.